Intra-Empyema Antibiotic Administration: A Case Report - Hakemi, Laleh; Kolivand, Pirhossein; Khodashenas Firoozabadi, Naereh (Archives of The Medicine and Case Reports, 2024)
Untreated empyema has a great morbidity and is potentially lethal. The usual approach for treatment is intravenous antibiotics together with chest tube insertion or thoracoscopic/ surgical interventions. The patient was a 32-year-old man with spinal muscular atrophy and severe intercostal muscular weakness presented with localized pleuritic chest pain and fever. The cause was diagnosed to be parapneumonic empyema. In this case, invasive approaches would potentially exacerbated chest musculature weakness. Other non-invasive managements CT-guided needle drainage and intravenous antibiotic therapy were tried and proved to be ineffective for the patient and the next invasive step would pose considerable risk to the patient. Intra-empyemic antibiotic administration through a small tube catheter was successfully effective without any recurrence. This method was non-invasive with no significant risk to the patient, had a low cost and was accepted by the patient. It was shown to be effective without any complication and saved the patient from performing an invasive procedure. This non-invasive approach may be used in those patients who are of high risk for invasive procedures. Also, potentially it may be used as one of the first line approaches before performing more invasive modalities.